The Umdet ul-Ahbar and the Turkic Narrative Sources for the Golden Horde and the Later Golden Horde - Uli Schamiloglu (Золотоордынское обозрение)
This paper presents in summary form results of the author’s study of the Turkic-Muslim sources. A number of Turkic narrative sources are preserved to us from the post-Golden Horde time, i.e. period of the successor States of the Golden Horde of the 15th–18th centuries. These narrative sources (mainly chronicles) are of fundamental importance for the study of the Eurasian history in the 13th–18th centuries. Since most of these works are available only in the original Turkish, they remain inaccessible and sometimes even unknown to the main part of modern scholars. Therefore, the author provides an overview of these historical writings, together with a more detailed study of one particular work, “Umdet ul-Ahbar / Umdetul-ahbar”. He expresses the hope that this review will contribute to the integration of the Turkic sources in the study of the western Eurasian history. This article contains several examples showing how useful can be this later source for understanding the history of the ulus of Jochi in the 13th century. The author pays special attention to this source’s information both about the existence of “ruling clans (tribes)” and on the role of the Karachi beys and kurultay in the government of the ulus of Jochi and post-Golden Horde States. The author emphasizes the role of Shiban and his descendants in determination of the Jochid foreign policy, in the implementation of their conquests in the West and distribution of the uluses in Eastern Europe and, in particular, in the Crimea. Although the later Turkic-Muslim sources require a more detailed analysis, this article represents the first pioneering step in this direction.